Learning from mistakes when reporting urgent and emergency vascular studies. Issue 3 (March 2022) - Jenkins, P.; MacCormick, A.; Stokes, J.; Lyall, F.; Rogers, A.; Gafoor, N.
Abstract : The majority of out-of-hours cases relate to neurological, chest, and gastrointestinal pathologies with acute vascular cases being encountered less commonly. Trainees and exposure of non-vascular/interventional radiology (IR) consultants to angiographic imaging is often limited in working hours and this may lead to reporting on-call cases outside of normal daytime practice. In a recent local review, a number on-call vascular studies were found to contain a number of vascular-related discrepancies. Vascular reporting is a complex subspecialty, which comprises many clear diagnoses (large vessel occlusions, large vessel aneurysms, or dissections); however, also several subtle and complex abnormalities. These more subtle abnormalities, at times, require dedicated vascular specialist review to ensure subtle findings are communicated appropriately to the clinical team. The recent increased complexity of endovascular treatments and their complications has also provided further challenge for the non-specialist reporter. Similarly, improved imaging techniques have allowed for non-obvious but significant findings that may require urgent management, such as small aneurysms and dissection flaps. We will review a range of key vascular findings that demonstrate learning opportunities, particularly within the acute and on-call settings. These will include gastrointestinal haemorrhage, subtle aortic pathologies, head and neck vascular emergencies, small to mid-sized vessel injuries and imaging of post-procedural complications. Educational hints and tips will be provided to enable learning from mistakes encountered by trainees and non-vascular specialist radiologists in the on-call or urgent reporting settings, and these will be reviewed with reference to the literature.